1982
DOI: 10.3758/bf03212267
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation of incentive gain

Abstract: In four experiments, the once daily availability of saccharin (.15%) preceded the availability of sucrose (32% or 2%). Experiment 1 showed that the intake of saccharin was reduced when it preceded 32% sucrose but not when it preceded 2% sucrose, as compared with saccharin-alone conditions. Experiment 2 showed that less saccharin was consumed when the saccharin preceded sucrose by 5 min than when there was a 30-min intersolution interval. Experiment 3 replicated this finding and showed that the presentation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
159
3
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 27 publications
11
159
3
2
Order By: Relevance
“…Studies were not designed to distinguish the mechanisms responsible for reductions in home-cage or predeprivation chow intake. However, several findings support the interpretation that chow hypophagia at the first feeder was a form of anticipatory negative contrast (Flaherty and Checke, 1982;Flaherty and Rowan, 1986;Flaherty et al, 1995) and not energy homeostatic compensation for accruing weight gain, lasting satiety, or successive negative contrast. First, there was no concurrent or prospective relation between differences in weight gain and the magnitude of chow hypophagia (unlike strong individual differences seen in chow hypophagia).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Studies were not designed to distinguish the mechanisms responsible for reductions in home-cage or predeprivation chow intake. However, several findings support the interpretation that chow hypophagia at the first feeder was a form of anticipatory negative contrast (Flaherty and Checke, 1982;Flaherty and Rowan, 1986;Flaherty et al, 1995) and not energy homeostatic compensation for accruing weight gain, lasting satiety, or successive negative contrast. First, there was no concurrent or prospective relation between differences in weight gain and the magnitude of chow hypophagia (unlike strong individual differences seen in chow hypophagia).…”
Section: Discussionmentioning
confidence: 68%
“…Such a learned change in food acceptance may increase risk for body weight dysregulation and eating disorders because of the increased role placed on sensoryhedonic, rather than nutritional, properties of food for controlling intake (Wardle et al, 2001). Perhaps an analog of this learned change in food acceptance, negative contrast in rodents refers to the hypophagia of an otherwise acceptable tastant that results from having predictably received access to a more preferred substance either immediately before (successive negative contrast) or subsequent to (anticipatory negative contrast) that substance (Flaherty and Checke, 1982;Flaherty and Rowan, 1986;Flaherty et al, 1995). Contrast effects have been studied previously using limitedly available (3-5 min) sweet solutions in weight-restricted rats, but have not yet been well-studied vis-à-vis day-to-day food acceptance/intake in subjects' self-determining body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, using both response-dependent (Williams, 1976a(Williams, , 1979(Williams, , 1981Williams & Wixted, 1986;Wilton & Gay, 1969) and response-independent (Farley , 1980; Williams, 1976b) schedules have demonstrated that a major portion of the contrast effect in a multiple schedule is produced by variation in the reinforcement rate following a target component. Moreover, other investigators , using procedures very different from free-operant multiple schedules, have obtained similar results (Bacotti, 1976;Flaherty & Checke, 1982;Flaherty & Rowan , 1985. A critical issue raised by these findings is the mechanism producing such a contrast effect.…”
supporting
confidence: 49%
“…While it is the case that rats clearly avoid intake of a taste cue when paired with a putatively aversive US, such as LiCl, for example, in 1982 Flaherty and Checke [37] reported that rats also avoid intake of a saccharin CS when paired, in once daily sessions, with a highly preferred 32% sucrose solution. This phenomenon was referred to as an anticipatory contrast effect because reduced intake of the saccharin cue was thought to be due to anticipation of the availability of the preferred sucrose reward in the very near future.…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 99%